Wolfram Function Repository
Instant-use add-on functions for the Wolfram Language
Function Repository Resource:
Try to find a counterexample to an equational hypothesis in a given system of axioms
ResourceFunction["FindEquationalCounterexample"][hyp,axms] tries to find an equational counterexample to the symbolic hypotheses hyp using the axioms axms. |
expr1⩵expr2 | assertion of equality |
ForAll[vars,stmt] | assertion that stmt is true for all values of vars |
Find a counterexample to an elementary hypothesis in group theory:
In[1]:= |
![]() |
Out[1]= |
![]() |
Show the counterexample association:
In[2]:= |
![]() |
Out[2]= |
![]() |
Generate a function to verify that this is a valid counterexample to the hypothesis:
In[3]:= |
![]() |
Out[3]= |
![]() |
In[4]:= |
![]() |
Out[4]= |
![]() |
Generate a function to verify that this counterexample is consistent with the underlying axioms:
In[5]:= |
![]() |
Out[5]= |
![]() |
In[6]:= |
![]() |
Out[6]= |
![]() |
Find a counterexample to a more sophisticated hypothesis in group theory:
In[7]:= |
![]() |
Out[7]= |
![]() |
Show the counterexample association:
In[8]:= |
![]() |
Out[8]= |
![]() |
Generate a function to verify that this is a valid counterexample to the hypothesis:
In[9]:= |
![]() |
Out[9]= |
![]() |
In[10]:= |
![]() |
Out[10]= |
![]() |
Generate a function to verify that this counterexample is consistent with the underlying axioms:
In[11]:= |
![]() |
Out[11]= |
![]() |
In[12]:= |
![]() |
Out[12]= |
![]() |
FindEquationalCounterexample supports hypotheses formulated in any equational axiom system, including Wolfram's shortest possible axiom for Boolean algebra (finding a counterexample to the hypothesis that the Nand operator is associative):
In[13]:= |
![]() |
Out[13]= |
![]() |
Show the counterexample association:
In[14]:= |
![]() |
Out[14]= |
![]() |
Generate a function to verify that this is a valid counterexample to the hypothesis:
In[15]:= |
![]() |
Out[15]= |
![]() |
In[16]:= |
![]() |
Out[16]= |
![]() |
Generate a function to verify that this counterexample is consistent with the underlying axioms:
In[17]:= |
![]() |
Out[17]= |
![]() |
In[18]:= |
![]() |
Out[18]= |
![]() |
Ring theory (finding a counterexample to the hypothesis that every ring is commutative):
In[19]:= |
![]() |
Out[19]= |
![]() |
Show the counterexample association:
In[20]:= |
![]() |
Out[20]= |
![]() |
Generate a function to verify that this is a valid counterexample to the hypothesis:
In[21]:= |
![]() |
Out[21]= |
![]() |
In[22]:= |
![]() |
Out[22]= |
![]() |
Generate a function to verify that this counterexample is consistent with the underlying axioms:
In[23]:= |
![]() |
Out[23]= |
![]() |
In[24]:= |
![]() |
Out[24]= |
![]() |
Equational Presburger arithmetic (finding a counterexample to the hypothesis that every integer is equal to its negation):
In[25]:= |
![]() |
Out[25]= |
![]() |
Show the counterexample association:
In[26]:= |
![]() |
Out[26]= |
![]() |
Generate a function to verify that this is a valid counterexample to the hypothesis:
In[27]:= |
![]() |
Out[27]= |
![]() |
In[28]:= |
![]() |
Out[28]= |
![]() |
Generate a function to verify that this counterexample is consistent with the underlying axioms:
In[29]:= |
![]() |
Out[29]= |
![]() |
In[30]:= |
![]() |
Out[30]= |
![]() |
Find a counterexample from a list of axioms:
In[31]:= |
![]() |
Out[31]= |
![]() |
Express the axioms as a conjunction:
In[32]:= |
![]() |
Out[32]= |
![]() |
Find a counterexample to a list of hypotheses:
In[33]:= |
![]() |
Out[33]= |
![]() |
In[34]:= |
![]() |
Out[34]= |
![]() |
Express the hypotheses as a conjunction:
In[35]:= |
![]() |
Out[35]= |
![]() |
This work is licensed under a Creative Commons Attribution 4.0 International License